FORMALIN DENGAN BERBAGAI PELARUT TIDAK EFEKTIF UNTUK MENCEGAH PERKEMBANGAN TELUR ASCARIS LUMBRICOIDES - Ni Putu Aryadnyani (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Formalin is a preservative for faeces containing parasites. The formalin that frequently usedis formalin10% in distilled water, but it could also be dissolved in a 0.85% NaCl or sodiumphosphate buffer. The 0.85% NaCl serves to maintain the osmosic pressure of cell, while thebuffer solution serves to maintain the stability of pH of the solution. Purpose this research isto determine whether there are differences in the ability of 10% formalin dissolved indistilled water, 0.85% NaCl and sodium phosphate buffer in terms of maintaining themorphology of cell and prevent the development of Ascaris lumbricoides eggs. This is anexperiment research using the randomized posttest control group design. This research usingthree treatments, there are faeces added with formalin 10% in distilled water; 0.85% NaCl orsodium phosphate buffer; and control without adding the formalin 10%. Each treatmentconsists of 9 replication. Control and treatment groups are observed microscopically everyday. Based on the research. There is no difference in eggs cell morphology and developmentof Ascaris lumbricoides eggs in all treatments. According to Kruskal Wallis and MannWithney test, P count > 0.05 which means there is no significant difference in time needed byAscaris lumbricoides eggs to become infective in every treatment. Formalin 10% in varioussolvents is not effective as faeces preservatives, in particular to prevent the development ofAscaris lumbricoides eggs due to they have already developed in average of 10 days.